The biocultural practice of the Mayan milpa and human rights in Yucatan - Batllori Sampedro, Eduardo Adolfo (2023)
The development of Mayan communities largely depends on the natural environment, and on the slash-and-burn agricultural model based on the milpa, which represents the ancient biocultural system that provides them with sustenance. This study aims to demonstrate that Mayan indigenous families are embedded within a legal framework that regulates access to natural resources, leaving the milpero peasant without options for economic, social and cultural reproduction. Under these premises, the legal environment that regulates access to natural resources of Mayan communities is analyzed, which encourages investment in the rural sector. However, the public policies and entities created for their application act in a sectorial, thematic and fragmented manner, combining inequity in ownership and in the use of resources for commercial exploitation, with a tendency towards concentration and centralization in the appropriation of the wealth generated. Despite the fact that environmental regulations admit the possibility that Mayan milpero peasants take advantage of the by-products of the agronomic biocultural system for self-consumption, in fact they are considered environmental offenders, thus violating the fundamental rights of individuals and indigenous communities. Two scenarios are proposed that allow the development of Mayan producers in Yucatan, as a fundamental part of human rights: 1. A scenario from the perspective of the individual producer, which takes place in an economic and environmental context of sustainability, and 2. A scenario from the perspective of the Mayan indigenous community, with an agroecological perspective of sustainability. The study reflects from the perspective of human ecology and its relationship with the practice of the ancient milpa system.